METHODOLOGY OF RESEARCH OF FSM OPTIMIZATION METHODS FOR FPGA - Grytsenko, A.A.; Zelenyova, I. J.; Siroshtan, S.Y.; Tatolov, E.R. (Radio Electronics, Computer Science, Control, 2013)
Methodology of research of known FSM optimization methods for modern FPGAs is proposed. Such methodology consists of different FSM generation, optimization, synthesis, verification stages and can be implemented using parallel and distributed systems. That approach can lead to the efficient results because of methodology nature. The general idea is to figure out the necessary tools and algorithms to prove, that optimized model of FSM has the same behavior as initial model. The structure of standard and specialized software tools for methodology implementation is demonstrated and analyzed. The results of methodology approbation using well-known FSM optimization method targeting Altera FPGAs are pointed out.